Advancing Educational Practice: Plotagon Story Media Implementation in Arabic Language Learning - Nafisah, Ainun; Anam, Syamsul; Maulana, Asep (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Listening skills are the main skills that students must master in learning Arabic before mastering other skills. This requires educators to be more creative in choosing and using learning media to achieve good learning outcomes. One of the media in improving listening skills that can be used is Plotagon Story-based animation media. This study aims to determine the effectiveness of using Plotagon Story-based animation media in improving listening skills. This study uses quantitative research methods with the type of Quasi Experimental Design with Non-Equivalent Control Group Design. The results of the analysis show that there is an effectiveness of using plotagon story-based animation media in improving listening skills, which is in the moderate category. The benefit of this research is to provide an overview of how animated media can overcome challenges in learning Arabic, especially in listening skills. The results of this study are expected to be a reference for educators in designing learning media that are more effective and innovative, and make a positive contribution to increasing student competence in learning Arabic listening skills.